Shifting relationships with nature through schools: exploring the social and spatial context for transformative sustainability education - Matteo Giusti; Vivika Mäkelä; Abigail Garbett Skagerlid; Michiru Nagatsu (Ecology and Society)
Transformative sustainability education has emerged as a vital approach for addressing the value crisis at the root of biodiversity loss, climate change, and socio-environmental injustices in the Anthropocene. Although schools are ideally positioned to drive this transformation, nature-based education often evaluates and targets individuals in isolation from their contexts. We examine how the spatial and social contexts of schools influence changes in human–nature relationships (HNR). We apply the same evaluative framework to two distinct educational settings: rural schools in Brazil, to investigate the contextualization of rural education within daily life, and urban forest preschools in Sweden, to investigate the ecological enablers surrounding meaningful nature-based activities. In Brazil, interviews with 32 students revealed that those students attending schools embedded in the local community developed a more profound, multifaceted, and more spiritual HNR, alongside a higher commitment to caring and advocating for nature conservation, compared with students in the conventional rural school. In Sweden, an analysis of 953 nature-based activities in three forest preschools indicated that the forests, trees, and diverse flora and fauna were the ecological catalysts for most mind-expanding, awe-inspiring, and overall meaningful nature experiences. Across both case studies, our analysis indicates that aligning pedagogical practices with the affordances and constraints of the surrounding social-ecological context is essential for encouraging shifts in HNR. Our findings underscore that the extent to which nature-based education can effectively be transformative depends on what the surrounding social-ecological context allows, promotes, or restricts. Therefore, embedding educational practices in their context and focusing on ensuring regenerative compatibility between educational activities and their local social-ecological system is central. Toward this goal, we further advance the BeNature framework; a transdisciplinary tool for designing and evaluating curricula in transformative sustainability education.